2018
DOI: 10.1108/sc-05-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Gendered assisted desistance: a decade from Corston

Abstract: Purpose The purpose of this paper is to examine the role of assisted desistance from the perspective of women involved in the criminal justice system. It focusses on two community projects set up in the aftermath of the 2007 Corston Report, Northshire Women’s Centres (WCs) and the Housing for Northshire project. Design/methodology/approach Through analysis of a year of observation in these settings and 23 narrative interviews with staff and service users, the paper notes the differences between risk-focussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Socio-structural barriers are acknowledged by the evidence-base to act as considerable obstacles to successful desistance (Best, 2016). When it comes to women's desistance, research has identified the significant stigmatic barriers experienced when attempting to reimagine their social identities; the shame and guilt they experience at higher levels than male desisters (Gålnander, 2020;Masson and Österman, 2017); but also, the benefits which desistance-focussed support can have (Barr, 2018). The women interviewed explored their own stigmatised identities during their interviews.…”
Section: Discussion: Integrating Women Partner's Voices Into the Desi...mentioning
confidence: 99%
“…Socio-structural barriers are acknowledged by the evidence-base to act as considerable obstacles to successful desistance (Best, 2016). When it comes to women's desistance, research has identified the significant stigmatic barriers experienced when attempting to reimagine their social identities; the shame and guilt they experience at higher levels than male desisters (Gålnander, 2020;Masson and Österman, 2017); but also, the benefits which desistance-focussed support can have (Barr, 2018). The women interviewed explored their own stigmatised identities during their interviews.…”
Section: Discussion: Integrating Women Partner's Voices Into the Desi...mentioning
confidence: 99%
“…McNeish and Scott (2014) highlight women's experiences of violence and abuse are often perpetrated by family members. However, the response is often only addressed at an agentic level, with the structural forces of patriarchy neither considered nor discussed (Barr, 2018). In addition, when men are involved in the lives of women tangled in the criminal justice system it is often through their role in promoting criminal behaviour (Leverentz, 2006) challenging the ability to separate criminal behaviour and victimisation (Gomm, 2013).…”
Section: Exploring Relational Networkmentioning
confidence: 99%
“…The limited positive and prosocial ties available to criminalised women within their wider relational networks can make relationships with practitioners, through probation or partner agencies, especially important (Morash et al, 2014). Criminalised women's experiences evidence a lack of flexibility and gender sensitive working in probation delivery, especially when women are single mothers with caring responsibilities (Barr, 2018). This demonstrates how practice requires a recognition of whole relational networks (Farmer, 2019;Rutter, 2019) to move beyond individualised responsibility and recognise the complexities of women's circumstances, experience and vulnerabilities which need to be taken into account (Ö sterman and Masson, 2017) to move beyond equality and into practices which evidence equity and justice.…”
Section: Recognising Practice-based Challengesmentioning
confidence: 99%
“…En Europe, les corpus criminologiques portant sur le désistement et la réhabilitation ont été en dialogue, voire se sont entremêlés, depuis les années 2000 (voir surtout Burke, Collett et McNeill, 2018 ;Ward et Maruna, 2007). temps » et gagneraient à être remplacés par un concept unique et hybride comme le « désistement assisté » (voir Barr, 2018 ;King, 2013 ;McNeill, 2006), qui rapprocherait ces deux domaines de recherche.…”
Section: Introductionunclassified